PARQUES NACIONAIS BRASILEIROS E AS CONCESSÕES DE SERVIÇOS DE USO PÚBLICO JUNTO À INICIATIVA PRIVADA - Geórgia Vitória Vieira Rocha; Luiz Renato Vallejo (Anais do Uso Público em Unidades de Conservação, 2026)
Partnerships with the private sector are adopted in several countries to improve visitor facilities in protected areas, such as national parks. The goal of this work is to present an overview of the management of Brazilian national parks (NPs) with contracts for the concession of public use support services to private initiatives, up until the year 2020. The study was developed through descriptive and exploratory research, using legislation, websites, and official platforms of the Federal Government, mainly the “Instituto Chico Mendes de Conservação da Biodiversidade”. The early stages of the study consisted of identifying all of Brazil's national parks and characterizing them in terms of the size of their area in hectares, year of establishment, region, biome, location, infrastructure, management plan, visitation, and ticket charging. Later, the current concession contracts for visitor support services were analyzed in seven parks: Chapada dos Veadeiros National Park, Tijuca National Park, Iguaçu National Park, Itatiaia National Park, Pau Brasil National Park, Fernando de Noronha Marine National Park, and Serra dos Órgãos National Park. Based on the evidence found, it was concluded that the concession models in place in 2020, while allowing for improvements in visitor management, do not explicitly include initiatives for biodiversity conservation and the protection of natural resources.